Bivalirudin Attenuates Thrombin-Induced Endothelial Hyperpermeability via S1P/S1PR2 Category: Original Articles - Ye, Haowen; Zhang, Yizhi; Huang, Yihui; Li, Biao; Cao, Ruhao; Dai, Libing; Huang, Bin; Tian, Pingge; Li, Li; Han, Yaling (Frontiers in Pharmacology, 2021)
1.1 Aims: To explore the role of the S1P/R pathway in thrombin-induced hyperpermeability (TIP) in HUVESs and to test whether bivalirudin can reverse TIP via the S1P-S1PRs pathway. 1.2 Methods and Results: Using western blot, we demonstrated that human umbilical vein endothelial cells (obtained from ATCC, CRL-1730) that were cultured with 2 U/ml thrombin showed significantly increased S1PR2 expression. Such increment was attenuated by JTE-013 pretreatment and by the presence of bivalirudin. As a surrogate of cytoskeleton morphology, phalloidin staining and immunofluorescence imaging were used. Blurry cell edges and intercellular vacuoles or spaces were observed along thrombin-exposed HUVECs. The presence of JTE-013 and bivalirudin attenuated such TIP morphological change and the presence of heparin failed to show the protective effect. Transwell chamber assay and probe assay were used to measure and compare endothelial permeability in vitro. In the Transwell chamber assay, increased TIP was observed in HUVECs cultured with thrombin, and coculture with bivalirudin, but not heparin, alleviated this increase. JTE-013 treatment yielded to similar TIP alleviating effect. In vivo, an Evans blue assay was used to test subcutaneous and organ microvascular permeability after the treatment of saline only, thrombin + saline, thrombin + bivalirudin, thrombin + heparin, or thrombin + JTE-013. Increased subcutaneous and organ tissue permeability after thrombin treatment was observed in thrombin + saline and thrombin + heparin groups. All animal procedures were strictly performed under the regulation of Guide for the Care and Use of Laboratory Animals Eighth Edition. 1.3 Conclusion: S1PR2 mediates TIP by impairing vascular endothelial barrier function. Unlike heparin, bivalirudin effectively blocked the thrombin-induced increase in S1PR2 expression and TIP in vitro and in vivo, suggesting the novel protective effect of bivalirudin and that bivalirudin may be beneficial in patients requiring intravenous anticoagulation.